PENGARUH FEE BASED INCOME TERHADAP TINGKAT PROFITABILITAS KELOMPOK BANK BERDASARKAN MODAL INTI (KBMI) III - Mochamad Surya Fadillah, (2021)
The development of technology today encourages banks to make efforts in improving services through banking services in order to achieve customer satisfaction. Services provided by the bank seem to be diverted into the digitization system to facilitate customers in making transactions. Banking digitization system aims to provide a sense of ease, speed and security in transactions. The perceived ease can increase customer confidence in banking. So that banking services can add to the bank's income which is included in the non-interest income component. The income earned from non-interest income is very important to increase, because it provides a definite thing with very little risk. The increase in non-interest income may also affect the bank's operating profit. Banks that always earn profit in every period can be said to be a healthy bank. The bank's health level can be measured using profitability ratios. Profitability ratio is used to determine the bank's ability to earn profit with assets and capital owned. So the higher the profitability level of the bank, the more interested customers or investors to entrust some of their money to be managed properly.